Visual performance in myopic adolescents fitted with pupil-optimised multifocal soft contact lens (Annals of Medical Research, 2024)
Aim: This study aims to assess the influence of a newly developed pupil-optimized multifocal soft contact lens (MFSCL) in comparison to single-vision contact lenses (SVCL) on visual performance among adolescent myopes.Materials and Methods: Myopic adolescents, aged 14 to 18 years, who were habitual SVCL users, were subjected to a trial involving MFSCL with a mid-addition power. Various visual parameters including distance and near visual acuity (VA), maximum reading speed (MRS), reading acuity, contrast sensitivity, and stereoacuity under photopic conditions were measured for MFSCL and compared to SVCL.Results: No statistically significant differences were observed between SVCL and MFSCL in terms of near VA, MRS, contrast sensitivity, and stereoacuity (p > 0.05 for all). However, a decrease in distance VA was noted with MFSCL (p = 0.021). Moreover, reading acuity, which denotes the smallest print size comprehensible without significant errors, was found to be smaller when using MFSCL (p < 0.001).Conclusion: In adolescent myopic patients, mid-add power in MFSCL did not significantly impact near VA and contrast sensitivity when compared to SVCL, while a decrease in distance VA was observed. Moreover, MFSCL did not affect reading speed but did enable the reading of smaller font sizes.
Keywords: Adolescent; Multifocal soft contact lens; Myopia; Reading speed; Single vision contact lens; Visual acuity